2019
DOI: 10.1155/2019/2603435
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Deficiencies in Branched-Chain Fatty Acids and Staphyloxanthin inStaphylococcus aureus

Abstract: Staphylococcus aureus is a well-known human pathogen with the ability to cause mild superficial skin infections to serious deep-tissue infections, such as osteomyelitis, pneumonia, and infective endocarditis. A key to S. aureus infections and its pathogenicity is its ability to survive in adverse environments, especially at lower temperatures, by regulation of its cell membrane. Branched-chain fatty acids (BCFAs) and staphyloxanthin have been shown to regulate membrane fluidity and staphylococcal virulence. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
(60 reference statements)
4
11
0
Order By: Relevance
“…Demonstrating that the acylation of glycosyl-4,4-diaponeurosporenoate mediated by CrtO enzyme is not exclusive to C15 and C17 fatty acids, as initially reported (Marshall and Wilmoth, 1981a), thus, C13 to C20 fatty acid chains that have been previously reported on the SA401 strain (Perez-Lopez et al, 2019) and other wild type S. aureus strains (Braungardt and Singh, 2019;Sen et al, 2016) were observed bonded to Glu-4.4'-DNPA core. The broad specificity of the acyltransferase CrtO was also reported in E. coli mutants with the formation of STX analogues derivatives that include C14 and C16 fatty acids and other fatty acids of different lengths of not yet characterized (Kim and Lee, 2012).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Demonstrating that the acylation of glycosyl-4,4-diaponeurosporenoate mediated by CrtO enzyme is not exclusive to C15 and C17 fatty acids, as initially reported (Marshall and Wilmoth, 1981a), thus, C13 to C20 fatty acid chains that have been previously reported on the SA401 strain (Perez-Lopez et al, 2019) and other wild type S. aureus strains (Braungardt and Singh, 2019;Sen et al, 2016) were observed bonded to Glu-4.4'-DNPA core. The broad specificity of the acyltransferase CrtO was also reported in E. coli mutants with the formation of STX analogues derivatives that include C14 and C16 fatty acids and other fatty acids of different lengths of not yet characterized (Kim and Lee, 2012).…”
Section: Discussionsupporting
confidence: 68%
“…The number of studies focused on S. aureus membrane lipid composition has increased in recent years. Particularly, a great interest has been directed to a saccharolipid containing carotenoid, known as Staphyloxanthin (STX) (Braungardt and Singh, 2019;Perez-Lopez et al, 2019;Tiwari et al, 2018;Xue et al, 2019), a natural pigment with wellknown antioxidant properties (Mishra et al, 2011;Tiwari et al, 2018;Zhang et al, 2018), responsible for the characteristic color of S. aureus (Kim and Lee, 2012;Marshall and Wilmoth, 1981a), and associated with tolerance to oxidative stress (Clauditz et al, 2006;Liu et al, 2005;Olivier et al, 2009). However, STX also plays an essential role on the regulation of membrane mechanical properties, and has been shown to hinder the permeability of the membrane to cationic antimicrobial peptides, increasing the virulence and bacterial fitness of S. aureus (Crass et al, 2019;Mishra et al, 2011;Vogeser and Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fig 7A shows that, whereas addition of acetate has a minor effect on growth at 37°C, the growth at 25°C of both the wt and ΔcshA strain is markedly affected, resulting in a pronounced growth delay. Results are similar in the Δcrt derivates excluding any major effect of staphyloxathin production in the growth delay ( Fig 7B ), which is in accordance with a recent study where the respective impact of staphyloxanthin and BCFA production on growth was evaluated and showed that the second had a major impact whereas the first affected growth to a minor extent [ 31 , 32 ].…”
Section: Resultssupporting
confidence: 91%
“…Demonstrating that the acylation of glycosyl-4,4-diaponeurosporenoate mediated by CrtO enzyme is not exclusive to C15 and C17 fatty acids, as initially reported (Marshall and Wilmoth, 1981a), thus, C13 to C20 fatty acid chains that have been previously reported on the SA401 strain (Perez-Lopez et al, 2019) and other wild type S. aureus strains (Braungardt and Singh, 2019;Sen et al, 2016) were observed bonded to Glu-4.4'-DNPA core. The broad specificity of the acyltransferase CrtO was also reported in E. coli mutants with the formation of STX analogues derivatives that include C14 and C16 fatty acids and other fatty acids of different lengths of not yet characterized (Kim and Lee, 2012).…”
Section: Discussionsupporting
confidence: 68%